2021
DOI: 10.1016/j.breast.2020.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity and health-related quality of life after accelerated whole breast irradiation in 5 fractions with simultaneous integrated boost

Abstract: Introduction: Acceleration of radiotherapy in 5 fractions for breast cancer can reduce the burden of treatment. We report on acute toxicity after whole-breast irradiation with a simultaneous integrated boost in 5 fractions over 10e12 days. Material and methods: Acute toxicity and health-related quality of life (HRQoL) of 200 patients, randomized between a 15-or 5-fractions schedule, were collected, using the CTCAE toxicity scoring system, the Multidimensional Fatigue Inventory, EORTC QLQ-C30 and BR23 and the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…The FAST-Forward trial adopted 10 or 16 Gy in 2-Gy fractions[8, 9]; however, we assumed that a shorter schedule would be desirable. It has been reported that ultra-HF-WBI using simultaneous integrated boost (SIB) is tolerable in terms of acute toxicities [17,18]. SIB might represent a better alternative, as it does not prolong the treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…The FAST-Forward trial adopted 10 or 16 Gy in 2-Gy fractions[8, 9]; however, we assumed that a shorter schedule would be desirable. It has been reported that ultra-HF-WBI using simultaneous integrated boost (SIB) is tolerable in terms of acute toxicities [17,18]. SIB might represent a better alternative, as it does not prolong the treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other studies, a relatively short OTT in both treatment arms was achieved by using a RT schedule in 5 fractions, delivered over 10–12 days. The RT schedule in 5 fractions is still experimental, although the results from the YO-HAI5, FAST and FAST-FORWARD trials are promising [ [10] , [11] , [12] ]. The UK FAST trial (5 fractions over 5 weeks) and FAST-FORWARD trial (5 fractions over 5 days) showed, compared to 25 or 15 fractions, no significant differences in relapse rates or survival as expected based on radiobiology, nor an increase in normal tissue toxicity after 10 years and 5 years, respectively [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the 5-fractions schedule over 10–12 days no long-term randomized evidence exists. An interim analysis of the YO-HAI5 study, randomizing between 5 fractions over 10–12 days and 15 fractions over 3 weeks, showed less acute toxicity [ 12 ] and better short-term HRQoL for the 5 fractions schedule [ 14 ]. A matched-case analysis with patients treated in 15 fractions, showed less 2-year toxicity except for fibrosis outside of the tumour bed [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations